Polylactide containing nanoparticles - new carriers of active compounds - Słomkowski, S.; Gadzinowski, M.; Sosnowski, S.; Radomska-Galant, I. (Polimery, 2022)
Two amphiphilic block copolymers poly(L-lactide)-b-polyglycidol-b-poly(ethylene oxide) (PLA-b-PGly-b-PEOX) were synthesized: PLA-b-PGly-b-PEOX(I) with Mn equal 6260 (PLA), 510 (PGly) and 6600 (PEOX) and PLA-b-PGly-b-PEOX(II) with Mn equal 3600 (PLA), 500 (PGly) and 5500 (PEOX). Polyglycidol segment in PLA-b-PGly-b-PEOX(II) was modified in reaction with succinic anhydride - the reaction leading to conversion of -CH2OH groups of polyglycidol monomeric units to -CH2OC(O)CH2CH2COOH moieties with carboxyl groups [modified PLA-b-PGly-b-PEOX(II) was denoted as PLA-b-PGly-b-PEOX(IIc)]. Molecules of all three copolymers did self assemble in water into polymeric nanoparticles with number average diameters equal 20.0š0.8 nm [PLA-b-PGly-b-PEOX(I)], 20.9š0.3 nm [PLA-b-PGly-b-PEOX(II)] and 33š1 nm [PLA-b-PGly-b-PEOX(IIc)]. Critical aggregation concentration (CAC - a concentration above which nanoparticles are formed) was equal 1.55ź10-2, 7.0ź10-2 and 2.51ź10-1 g/L for PLA-b-PGly-b-PEOX(I), and PLA-b-PGly-b-PEOX(IIc), respectively. Nanoparticles were formed also in presence of pyrene and partition of pyrene between solution and nanoparticles was determined. For example, for concentrations of PLA-b-PGly-b-PEOX(II) and pyrene equal 1.95ź10-3 g/L and 4.94ź10-7 g/L the fraction of encapsulated pyrene was ca. 10 % whereas for the same concentration of pyrene but for higher concentration of PLA-b-PGly-b-PEOX(II), above 2.50ź10-1 g/L, the whole amount of pyrene was incorporated into nanoparticles. Profile of pyrene release from nanoparticles was bi-exponential with the rate constant for "fast" (kf) component equal 9.5ź10-2, 3.8ź10-2 and 1.5ź10-1 L/h, for PLA-b-PGly-b-PEOX(I), PLA-b-PGly-b-PEOX(II) and PLA-b-PGly-b-PEOX(IIc), respectively, and with the rate constant for "slow" (ks) component essentially the same for nanoparticles from all terpolymers equal (8.4š0.2)ź10-3 L/h. It has been suggested that "fast" rate describes the release of pyrene from shells of nanoparticles whereas the "slow" one describes the release from their cores.